PENGARUH METODE PEMBELAJARAN SOSIODRAMA TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI PADA MATA PELAJARAN BAHASA INDONESIA - Junari Junari; Farida Fitriani (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2019)
Sociodrama methods play an important role in increasing student creativity becausetheir used can help students in the learning process and was expected to increase creativity. But inreality there are still teachers who are not creative in teaching such as lecture learning methods andquestions and answers. The formulation of the problem in this study was. This research usedquantitative methods with 24 subjects. Data collection techniques used Questionnaire as the mainmethod, observation as a step to find information directly while the documentation as a supportmethod. Data analysis techniques used the chi square. Based on the results of data analysis inwhich X2 > X2-table was 10.757 > 9488 with a significance level of 5% in accordance with dataanalysis that has been obtained through research used the chi square formula, it turns out that thenull hypothesis (H0) proposed was rejected and alternative hypothesis (Ha) was accepted, then theresults of data analysis in this study are stated to be Significant. Thus it can be concluded that“There was The Effect of Sociodrama Method Towards Students’ Creativity Class XI inIndonesian Language Subjects at Al-Azhar Islamic High School West Lombok in Academic Year2019/2020.